A Lora-Based Geofencing System For Real-Time Elephant Movement Monitoring And Early Warning - Andika, Furqon; Azwar, Hamid; Indani, Wira; Diono, Muhammad (Journal of Electrical Engineering and Computer (JEECOM), 2026)
This research aims to develop an elephant movement monitoring system capable of transmitting data from a gateway to a server using the MQTT protocol and displaying information in real time via a web-based dashboard. This system is designed to support remote monitoring with low latency and a wide communication range. Test results show that the average data transmission time from the gateway to the server via the MQTT protocol is 1.44 ms, while the average notification delivery time to the user is 0.89 seconds. The system is capable of operating up to 1 km with an RSSI value of -105 dB, indicating stable communication at that distance. In addition, the developed dashboard was successfully deployed online, allowing users to monitor sensor data and device status in real time through an interactive and easy-to-use interface. The results of this study indicate that the developed system has efficient communication performance, low latency, and ease of monitoring, making it potentially applicable to various IoT applications based on remote monitoring.